PENGEMBANGAN INDIKATOR 4 C’s YANG SELARAS DENGAN KURIKULUM 2013 PADA MATERI PENYAJIAN DATA SMP/MTs KELAS VII SEMESTER 2 - Octaerdiyani, Debby; Sunardi, Sunardi; Kurniati, Dian (Kadikma, 2017)
Abstrak. The purpose of this research are to (1) develop 4C's indicator which is in line with the curriculum of 2013 in mathematics subject of second semester seventh grade of junior high school/MTS; (2) find out the result of 4C's indicator which is in line with the curriculum of 2013 in mathematics subject of second semester seventh grade of junior high school/MTS’s development. Indicator which is developed is an indicator which is in line with the curriculum of 2013 in mathematics subject of second semester seventh grade of junior high school/MTS. 4C’s Indicator is indicator that consists of 4 abilities namely (1) critical thinking; (2) creative; (3) communication; (4) collaboration. This research’s type is development research using modified Plomp’s model which is consists of 4 stages namely (1) the initial investigation phase; (2) the designing phase; (3) the realization/construction phase; (4) the test, evaluation, and revision phase. The development’s result of the 4C’s Indicator which is line with the curriculum of 2013 in mathematics subject of second semester seventh grade of junior high school/MTS. Based on the results of the development of this 4C’s indicator indicates that it is said to be proper to be used in learning. Kata Kunci : Pengembangan, Indikator, 4C’s, critical thinking, creative, communication, collaboration, penyajian data